2021
DOI: 10.1248/bpb.b20-00849
|View full text |Cite
|
Sign up to set email alerts
|

Glucosyl Hesperidin Has an Anti-diabetic Effect in High-Fat Diet-Induced Obese Mice

Abstract: Glucosyl hesperidin (GH) is a water-soluble derivative of hesperidin, a citrus flavonoid. GH has various pharmacological effects, such as hypolipidemic and hypouricemic effects, and may therefore be a useful supplement or drug. In the present study, we evaluated the effects of long-and short-term intake of GH on hyperglycemia and macrophage infiltration into the adipose tissue of high-fat diet (HFD)-fed mice. Longterm (11-week) consumption of GH tended to reduce body weight and the fasting blood glucose concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Hesperidin is less distributed than rutin but is also a strong multi-target antidiabetic agent according to the computational measurements. These findings are in line with the literature; hesperidin is considered to have preventive and/or therapeutic effects against DM as it regulates glucose and lipid metabolism [170,171]. Overall, flavonoids are an interesting pool of antidiabetic compounds and further study is needed to probe the structural characteristics of flavonoids that are mainly linked with antidiabetic activity.…”
Section: Ppard 3peqsupporting
confidence: 87%
“…Hesperidin is less distributed than rutin but is also a strong multi-target antidiabetic agent according to the computational measurements. These findings are in line with the literature; hesperidin is considered to have preventive and/or therapeutic effects against DM as it regulates glucose and lipid metabolism [170,171]. Overall, flavonoids are an interesting pool of antidiabetic compounds and further study is needed to probe the structural characteristics of flavonoids that are mainly linked with antidiabetic activity.…”
Section: Ppard 3peqsupporting
confidence: 87%
“…The liver is the key site of lipid metabolism. The relative content of blood lipids in the human body is mainly regulated by hepatocytes, which convert cholesterol into bile acids and secrete bile to promote the digestion and absorption of fat in the intestine ( 52 , 53 ). When the liver function is damaged, the production and excretion of bile is hindered, resulting in abnormal lipid metabolism in the body.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kappel et al (2013) demonstrated that flavone glycosides enhance intracellular Ca 2+ concentration and inhibit the ionization of ATP-sensitive K + channels in pancreatic islets, a precursor to insulin synthesis. Long-term (11-week) consumption of growth hormone (GH) reduced body weight, fasting blood glucose concentration, glucose intolerance, and insulin resistance in mice fed an HFD (Yoshida et al, 2021). Furthermore, GH reduced macrophage infiltration into adipose tissue despite not affecting fat pad weight.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%